Uniformly-distributed Sb nanoparticles in ionic liquid-derived nitrogen-enriched carbon for highly reversible sodium storage. Issue 26 (12th June 2017) - Xu, Xin; Dou, Zhifeng; Gu, Erlong; Si, Ling; Zhou, Xiaosi; Bao, Jianchun
Abstract : We report a novel composite of Sb nanoparticles uniformly embedded in ionic liquid-derived nitrogen-enriched carbon (Sb@NC) obtained by pyrolysis of SbCl3 /1-ethyl-3-methylimidazolium dicyanamide (Emim-dca) as a promising anode material for sodium-ion batteries. Abstract : Antinomy (Sb) has received considerable attention as one of the most promising anode materials for sodium-ion batteries (SIBs) because of its high theoretical capacity and suitable working voltage. However, the large volume change of Sb during the alloying/dealloying process causes poor cycling stability and low rate capability, which hinder its practical application. Here, we substantially enhance the sodium storage performance of Sb by binding Sb nanoparticles in ionic liquid-derived nitrogen-enriched carbon (Sb@NC) via pyrolysis of an SbCl3 /1-ethyl-3-methylimidazolium dicyanamide mixture. The Sb@NC composite exhibits a high reversible capacity of 440 mA h g −1 at a current density of 100 mA g −1, superior rate performance of 285 and 237 mA h g −1 at the high current densities of 2 and 5 A g −1, respectively, and greatly improved cycle life of 328 mA h g −1 at the current density of 100 A g −1 after 300 cycles in the half cell of SIBs. In the full cell, the energy density of Sb@NC//Na3 V2 (PO4 )3 /C is approximately 147 W h kg −1 at a power density of 50 W kg −1 . Even at 2.37 kW kg −1, an energy density of around 65 W h kg −1 is still retained. The remarkably improved electrochemical performance could be assigned to the synergistic effect of nanoscale size, uniform distribution, and chemical coupling effect between Sb and ionic liquid-derived nitrogen-enriched carbon.